Previous statements of witnesses and experts in an annulled trial and the right to confront in the Peruvian criminal process (SCIÉNDO INGENIUM, 2022)
It was investigated why the use in the new oral trial of the previous statements of witnesses, experts and defendants, made in an annulled trial, and those provided before the Prosecutor's Office or the Judge during the investigations, favors the right to confront in Peru. The hypothesis was that, if they favor the aforementioned right of the procedural parties, because they allow to refresh the memory and show contradictions and inconsistencies that reduce the credibility of the deponents, which must necessarily be weighed when issuing the new sentence. As a data source, a sample of doctrinal positions of 05 authors was considered, as well as a survey of 120 criminal lawyers, in order to verify the hypothesis and propose a solution proposal. The results were presented in tables of statistical frequency and the analysis, inductive, deductive, and hermeneutical-dialectical methods were used for their discussion, which allowed to positively validate the hypothesis raised in relation to the previous statements of witnesses and experts, but not in what concerns the accused, considering that it affects their right not to incriminate themselves. Concluding in the need for express regulation in the Criminal Procedure Code.
Keywords: Right of Defense; Right to Confront; Test; Nullity